Ногоон бүсийн шинэсэн (larix sibirica ldb.) Ойн үрлэлт үрийн чанарт агаарын бохирдлын үзүүлэх нөлөө - Б, Удвал; Ц, Дашзэвэг (Proceedings of the Mongolian Academy of Sciences, 2017)
The study sites are located in green zones in Ulaanbaatar. Ulaanbaatar is situated in the central part of the country, in the Tuul river valley, at an average height of 1350 m above sea level. In recent year’s air pollution of Ulaanbaatar city has become the main problem of increasing population and coal burning in informal residential areas, industrial boiler, power plants, motor vehicles, household heating systems. We have established 8 sample plots, which are situated in western and east part of the city and separated from each other by 10, 15, 20, 30 km. We have evaluated all trees in the research plots according to Korchagin’s seed crop evaluation and results show that 2014 year has lower seed crops (1 category by Kraft’s classification) than that 2015 year (4 category by Kraft’s classification). The seed quality was examined by weight of 1000 seeds, germination energy, and germination capacity on every sample plots. The study results showed significant differences in seed quality among sample plots. We have evaluated all trees in the established plots according to (I) Kraft’s classification on tree growth performance and (II) scale categories properties of trees. As a result of the evaluation, research sites in Shadivlan, Yargait, Khurel Togoot, Zalaat has a common issue. That was reduced growth of trees due to improper human influence and air pollution. Finally, air pollution and recreation use in green zones of the city has direct impact on tree growth and general attribution of the forests.